DAMPAK KEBERADAAN PROSTITUSI BAGI MASYARAKAT (Studi Pada Cafe-Cafe di Daerah Panjang Kota Bandar Lampung) - Jayanthi, Mutia Irna; Ikram, Ikram (SOCIOLOGIE, 2013)
Prostitution as a social problem as is seen from the relation of cause and effect and its origin can not be known with certainty, but to brothels mation encountered in everyday life, therefore, the public in general will condemn the practice of prostitution should do actions to stop or at least be aware and inform the public impact that will arise from the practice of prostitution. The length of the harbor area is an area in which we have encountered many cafes that operate at night, these cafes provide plenty of entertainment for the guests who come, therefore most of the people living in the area have experienced their impact on everyday life to-day. The formulation of the problem in this research is the social impact of the existence of the cafes in the area long. Type of research used in this study is a qualitative in-depth interviews. Based on the research and discussion by the author it could be concluded that, the limited interaction between community, community was disturbed by the cafes is due to the strains of loud music coming from the cafe and public perception outside the Long bahwasannya their place is a place of prostitutionKeywords: Prostitution, cafes